Future’s Thinking Integration in the Preparation of Comprehensive Land Use Plans of the Local Government Units: A Systematic Literature Review - Gutierrez, Mila Grace (International Journal of Sustainability and Advanced Integrated Research, 2026)
This systematic literature review examined the integration of futures thinking into the preparation of Comprehensive Land Use Plans by local government units, with particular attention to its potential application in the Philippine planning context. The study was anchored in strategic foresight, scenario-based planning, adaptive and participatory governance, institutional capacity, and social-ecological resilience. A systematic literature review design was employed using descriptive evidence mapping, qualitative content analysis, comparative analysis, thematic synthesis, and gap analysis. A structured data-extraction matrix was used to analyze 45 publications issued from 2021 to 2026. The findings showed that 35.6 percent of the reviewed publications primarily addressed futures-thinking approaches, while 24.4 percent focused on climate adaptation and disaster resilience, another 24.4 percent examined sustainable land use and ecological systems, and 15.6 percent concentrated on governance and institutional capacity. Scenario planning emerged as the most consistently represented approach, supported by participatory visioning, spatial modeling, vulnerability assessment, and strategic foresight. The review found that futures thinking can strengthen environmental scanning, identification of uncertainties, development of alternative land-use scenarios, stakeholder participation, policy formulation, zoning, implementation, and adaptive monitoring. However, its integration was constrained by fragmented application, limited attention to social equity, inadequate institutional capacity, weak translation of scenarios into formal planning decisions, and the absence of direct empirical validation within Philippine LGU CLUP preparation. The study recommends pilot-testing the proposed literature-derived framework in selected Philippine LGUs, supported by stakeholder participation and capacity building. The study contributes to SDGs 9, 11, 13, 15, 16, and 17 by supporting innovative infrastructure planning, sustainable communities, climate action, ecosystem protection, effective institutions, and collaborative governance. Its sustainability impact lies in promoting more anticipatory, inclusive, resilient, environmentally responsible, and institutionally adaptive land-use planning.